2021
DOI: 10.1016/j.mtla.2021.101220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grinding and shot-peening on the near-surface microstructure of a maraging stainless steel

Abstract: The near-surface properties of maraging steels are key to controlling their mechanical properties. They can be tailored by surface treatments such as shot peening and can also be influenced by prior machining. This study aims at determining the respective roles of grinding and shot peening processes on the near-surface microstructure of Custom 465 maraging stainless steel. A combination of experimental techniques, including X-ray diffraction (XRD), transmission electron microscopy (TEM), and atom probe tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…According to the analysis of the gas phase ow characteristics in 4.1.1, the gas phase distribution at the bottom of the recovery bin shows that a part of the waste particles passing under the ba e 4 cannot enter the outlet pipe under the air ow after entering the bottom of the recovery bin, but enter the inlet port with the steel shot under the action of vortex and particle impact, this part of the waste particles cannot be recovered, and this part of the particles will not only cause the key parts of the blast machine blade Wear (some data show [5], when the content of waste particles in the shot every 1% increase, the wear of the blast machine blade increased by 2-3 times.) Also, during the shot peening process, the waste particles are discharged into the air through the shot peening process, causing particle dust pollution to the atmosphere.…”
Section: Waste Materials Movement Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analysis of the gas phase ow characteristics in 4.1.1, the gas phase distribution at the bottom of the recovery bin shows that a part of the waste particles passing under the ba e 4 cannot enter the outlet pipe under the air ow after entering the bottom of the recovery bin, but enter the inlet port with the steel shot under the action of vortex and particle impact, this part of the waste particles cannot be recovered, and this part of the particles will not only cause the key parts of the blast machine blade Wear (some data show [5], when the content of waste particles in the shot every 1% increase, the wear of the blast machine blade increased by 2-3 times.) Also, during the shot peening process, the waste particles are discharged into the air through the shot peening process, causing particle dust pollution to the atmosphere.…”
Section: Waste Materials Movement Characteristicsmentioning
confidence: 99%
“…Mobile shot blasting machine broke the traditional xed shot blasting machine can only be cleaned indoors traditional parts of the limitations of the shot blasting process to expand to the surface of the ship rust removal and strengthening [2], airport runway debonding repair, highway and bridge paint removal maintenance and various other elds, compared with other maintenance equipment, shot blasting treatment in the economy, environmental protection and e ciency has huge advantages [3]. Mobile shot blasting machine recycling device can realize the recycling of steel shot and automatic recycling of processing waste, but in the actual production and processing, the recycling rate of waste generated after shot blasting process is low [4], and the dust particles generated during the recycling process are easy to cause environmental pollution, construction personnel are prone to lung diseases caused by inhalation of large amounts of dust [5]. Studies have shown that a more e cient and environmentally friendly recycling e ciency is achieved when the waste recovery e ciency reaches 90% [6].…”
Section: Introductionmentioning
confidence: 99%